Implementasi Merdeka Belajar dalam Sokola Rimba di Taman Nasional Bukit Dua Belas Jambi - Jamil, Zawaqi Afdal; Nazari, Nazari; Aisyah, Siti (Yayasan Lembaga Studi Makwa, 2024)
This research was conducted with the aim of knowing the reality of Free Learning which is applied to Sokola Rimba in the Bukit Dua Belas National Park, Jambi Province. The history of the emergence of Sokola Rimba and Sokola Rimba in implementing Free Learning. The approach used in this study is a qualitative approach. The use of this qualitative approach is because the data to be disclosed is data in the form of opinions, views, comments, criticisms, and reasons. Data collection methods used by observation, interviews, and document review. The research subjects are the founders of the jungle school, Tumanggung, the leaders and students of the jungle school. The results of the study were: 1) the spirit of an initiator so that jungle people can communicate and interact normally with the world of information and technology so that the quality of life increases which ultimately makes jungle people able to compete fairly, 2) learning in jungle schools is carried out naturally, not there is a grade level grouping that shows the level of material that the jungle people must follow, 3) the attitude of groups and individuals in implementing jungle school is relatively low, the high mobility of jungle people in everyday life is a challenge for the jungle school implementation in carrying out the learning process less than optimal, access the road to enter the jungle forest which is relatively far away, and the availability of facilities and infrastructure for the jungle school which is relatively minimal is one of the main obstacles to organizing the jungle school, as well as geographical conditions where the distance between the huts and the houses where they live is relatively far away.